2019
DOI: 10.1016/j.omtn.2019.05.007
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA UCA1 Mediates Resistance to Cisplatin by Regulating the miR-143/FOSL2-Signaling Pathway in Ovarian Cancer

Abstract: The aim of this study was to explore the roles of the long noncoding RNA (lncRNA) urothelial carcinoma-associated 1 (UCA1) on cisplatin resistance in ovarian cancer and the underlying mechanisms. We investigated the expression of lncRNAs in 3 paired cisplatin-sensitive and cisplatin-resistant tissues of ovarian cancer by microarray analysis. The qRT-PCR analysis was to investigate the expression pattern of UCA1 in cisplatin-resistant ovarian cancer patient tissues and cell lines. Then we examined the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
106
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(106 citation statements)
references
References 23 publications
0
106
0
Order By: Relevance
“…and causes a variety of cancers including lung cancer [74]. The lncRNA UCA1 negatively regulated has-miR-143 expression in a dose-dependent manner in various cancer cells [75,76]. In our research, the lncRNA UCA1 not only as a regulator for hsa-miR-143 but other miRNAs (Fig.…”
Section: Discussionmentioning
confidence: 51%
“…and causes a variety of cancers including lung cancer [74]. The lncRNA UCA1 negatively regulated has-miR-143 expression in a dose-dependent manner in various cancer cells [75,76]. In our research, the lncRNA UCA1 not only as a regulator for hsa-miR-143 but other miRNAs (Fig.…”
Section: Discussionmentioning
confidence: 51%
“…Li et al suggested that lncRNA UCA1 was upregulated in cisplatinresistant patient tissues and cell lines. Knockdown of UCA1 inhibited cell proliferation and promoted the cisplatin-induced cell apoptosis in OC cells [13]. The expression of lncRNA ABHD11-AS1 in OC tissues was higher compared to normal ovarian tissue.…”
Section: Introductionmentioning
confidence: 91%
“…Li et al suggested that lncRNA UCA1 was upregulated in cisplatin-resistant patient tissues and cell lines. Knockdown of UCA1 inhibited cell proliferation and promoted the cisplatin-induced cell apoptosis in OC cells [13]. The expression of lncRNA ABHD11-AS1 in OC tissues was higher compared to normal ovarian tissue.…”
Section: Introductionmentioning
confidence: 91%